Pendidikan Anak dalam Keluarga Berdasarkan Kolose 3:21 - Ezra Tari; Talizaro Tafonao (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
This article aimed to describe the education of children in the family based on Colossians 3:21. This study used a sociological criticism approach by conducting a study of the text of Colossians 3:21 to analyze the Bible's view of children's education in the family. The conclusion of this textual study is educating children without violence. Paul reminded fathers in educating children to prioritize love as the basis for education in the family. The love of a father will be reflected in the lives of every child through communication and imprinted in an attitude of obedience and respect for parents. AbstrakArtikel ini bertujuan untuk mendreskripsikan pendidikan anak dalam keluarga berdasarkan Kolose 3:21. Penelitian ini menggunakan metode pendekatan kritik sosiologis dengan melakukan kajian terhadap teks Kolose 3:21untuk meng-analisis pandangan Alkitab tentang pendidikan anak dalam keluarga. Kesimpulan dalam kajian terhadap teks tersebut adalah mendidik anak tanpa adanya kekerasan. Paulus mengingatkan para ayah dalam mendidik anak-anak lebih mengutamakan kasih sayang sebagai dasar pendidikan dalam keluarga. Kasih sayang seorang ayah akan tercermin dalam kehidupan setiap anak melalui komunikasi dan terpatri dalam sikap taat dan menghormati orang tua.